088 Is there any improvement in 3D and 2D echocardiography determined left atrial volume following continuous positive airway pressure treatment in patients with obstructive sleep apnoea?. (22nd September 2015) - Butt, M; Dwivedi, G; Khair, O; Lip, G
Abstract : Background: Previous studies have reported a higher incidence of diastolic dysfunction indices in obstructive sleep apnoea (OSA). Chronic diastolic dysfunction causes structural and functional remodelling of left atrium resulting in increase in left atrial volume (LAV). Long-term continuous positive airway pressure (CPAP), an accepted treatment for OSA, has been shown to lead to improvement in diastolic function in OSA. However, it is still not known if long term CPAP treatment causes reduction in LAV (representing chronic diastolic dysfunction) in such patients. Methods: Accordingly, a total of 27 patients with moderate to severe OSA (aponea-hypopnoea index>15) were recruited. All patients underwent 3D echocardiography (3DE) for end-systolic LA volume calculation prior to CPAP treatment. LA volume was also calculated using conventional 2D echocardiography (2DE) methods (ie, elliptical and biplane area length). All OSA patients were then treated by CPAP (>20 weeks). 3DE and 2DE LAV measurements were repeated following successful CPAP treatment. Results: Mean duration of CPAP therapy was 20 weeks. Significant reduction in LAV was noted by all three methods following CPAP therapy (abstract 088 table 1 ). Conclusion: Long term successful CPAP treatment results in significant reduction in LAV, a marker for adverse prognosis, determined by 3D and 2DE techniques.